DOES SATISFACTION MATTER ? A PLS-SEM STUDY OF DISCIPLINE, ENVIRONMENT, AND PERFORMANCE IN CV LEO PUTRA MAKMUR - siti arbaatun; Efriyani Sumastuti Nastiti; Prianka Ratri Nastiti (STABILITY : Journal of Management and Business, 2025)
This study investigates whether job satisfaction significantly mediates the influence of work environment and work discipline on employee performance at CV Leo Putra Makmur, a growing agro-based MSME in Indonesia. Using a quantitative approach with data collected from 102 employees, the study applied Partial Least Squares Structural Equation Modeling (PLS-SEM) to examine direct and indirect relationships among variables. The results show that work environment has a significant effect on both job satisfaction and employee performance. Work discipline significantly affects performance but not job satisfaction. Interestingly, job satisfaction does not significantly influence performance, nor does it mediate the relationship between the independent variables and performance. These findings suggest that while a supportive environment and strong discipline drive performance, job satisfaction may not always play a central mediating role in MSME contexts. The study offers insights for managers aiming to improve productivity through targeted HR strategies.